Turning the Light on: The Ontario Historical Society and Museum Governance - Nelson, Robin (Ontario History)

(untitled) (The Ontario Historical Society, 2021)
Since 1953, the Ontario Historical Society (OHS) has played an important role in establishing the legislative and training framework within which museums in Ontario operate, providing the first recorded museum training workshops in Canada, establishing a newsletter to connect museums, and successfully advocating for provincial support to museums. This article considers the organization’s self-defined role in museum governance since the establishment of a provincial museum policy in 1981, asking: how has the OHS’s role evolved and why and how does their work contribute and relate to support for museums in Ontario more broadly? It examines the OHS’s role in publishing, training, and advocacy or capacity building in three periods. Most recently, the OHS’s focus has shifted to capacity building due to municipal amalgamation, governments’ divestment of heritage resources, and decreased government support for service organizations. Their role takes place within a broader network of relationships aiming to support museums based on the assumed value of heritage preservation and museum work rather than a call for excellence.